Local knowledge and perceptions of chimpanzees in Cantanhez National Park, Guinea‐Bissau. Issue 2 (1st October 2013) - Sousa, Joana; Vicente, Luís; Gippoliti, Spartaco; Casanova, Catarina; Sousa, Cláudia
Abstract Our study concerns local knowledge and perceptions of chimpanzees among farming communities within Cantanhez National Park, Guinea‐Bissau. We submitted a survey questionnaire to 100 people living in four villages in the Park to enquire about their knowledge of chimpanzee ecology and human–chimpanzee interactions. Local farmers live in close contact with chimpanzees, consider them to be more similar to humans than any other species, and attribute special importance to them primarily due to expectations of tourism revenue. Interviewees' responses, as a function of gender, village, and age, were analyzed statistically using non‐parametric tests (Mann–Whitney and Kruskal–Wallis). Age influenced responses significantly, while gender and village had no significant effect. Youngsters emphasized morphological aspects of human–chimpanzee similarities, while adults emphasized chimpanzee behavior and narratives about the shared history of humans and chimpanzees. Tourism, conservation, and crop raiding feature prominently in people's reports about chimpanzees. Local people's engagement with conservation and tourism‐related activities is likely to allow them to manage not only the costs but also the benefits of conservation, and can in turn inform the expectations built upon tourism. Am. J. Primatol. 76:122–134, 2014. © 2013 Wiley Periodicals, Inc.